Evidencias de validez de la Escala de Bienestar Social para la población brasileña - Paulo Roberto , Taborda de Souza (2026)
Health and well-being constitute a critical source of both financial and social capital for the sustainable development of countries and communities. In the Brazilian context, however, there is a notable shortage of validated instruments designed to assess well-being from an interrelational perspective. Thus, the present study aims to present evidence of the validity of the Social Well-being Scale for Brazil. The participants were 214 Brazilian subjects, 80 % women, aged between 18 and 77 years (M = 32.75; SD = 10.68), who completed the social well-being scale and the General Health Questionnaire (GHQ-12). The data were analyzed using confirmatory factor analysis. The results identified a five-factor model with satisfactory alphas (Social Integration: α = 0.80, ωt = 0.82; Social Acceptance: α = 0.84, ωt = 0.87; Social Contribution: α = 0.84, ωt = 0.83; Social Actualization: α = 0.66, ωt = 0.84; and Social Coherence: α = 0.63, ωt = 0.71; Total Scale: α = 0.89; ωt = 0.95) and adequate fit indices: CFI: 0.95; TLI: 0.94; RMSEA: 0.06 (C.I. = 0.05–0.07). The scale showed a significant association with the GHQ-12, providing validity evidence based on relations to other variables. The instrument contributes to the expansion of studies on social well-being in the Brazilian context.